ChemInform Abstract: Zinc Radical Transfer Based Modular Approach to Enantiopure Alkylidene‐β‐prolines from N‐(tert‐Butylsulfinyl)‐α‐(aminomethyl)acrylates. Issue 15 (24th March 2016) - Beniazza, Redouane; Romain, Elise; Chemla, Fabrice; Ferreira, Franck; Jackowski, Olivier; Perez‐Luna, Alejandro
Abstract: A modular entry to enantiopure (E)‐2‐substituted 3‐alkylideneprolines is disclosed in 5 or 6 steps from tert‐butanesulfinamide.